1, 2-Dialkynyldiboranes(4): B–B versus CC bond reactivity. Issue 16 (7th April 2022) - Schorr, Fabian; Arrowsmith, Merle; Fantuzzi, Felipe; Rempel, Anna; Braunschweig, Holger
Abstract : The B–B and CC bonds of 1, 2-dialkynyl-1, 2-diaminodiboranes(4) can be functionalised either on their own or successively using organic azides, hydroboranes, hydrogen and heavier halogens. Abstract : The reactivity of three 1, 2-dialkynyl-1, 2-diaminodiborane(4) derivatives, B2 (NMe2 )2 (CCR)2 (R = H, Me, SiMe3 ), towards small molecules known to react with both B–B and CC bonds was studied. With arylazides nitrene insertion into the B–B bond with concomitant loss of N2 was kinetically favoured in all cases. While reactions with sterically unhindered hydroboranes proceeded unselectively, sterically encumbered dimesitylborane cleanly added to both alkynyl moieties, resulting in the first examples of 1, 2-divinyldiboranes(4). In the presence of catalytic amounts of Pd/C room-temperature hydrogenation at 1 bar led to oxidative B–B bond cleavage and yielded the fully hydrogenated alkyl(amino)hydroborane products. These could be prevented from dimerising and isolated by complexation with an NHC ligand. Finally, stepwise halogenation of the B–B bond and the alkynyl groups afforded first the corresponding alkynyl(amino)haloboranes and then the amino(halo)(1, 2-dihalovinyl)boranes.